A hydrophobic material and its preparation method and application
By using NiCo2O4/Ni composite material to use the hydrophobic coating of fuel cell bipolar plates, the problem of prone to water flooding of bipolar plates is solved, excellent hydrophobicity and ice resistance are achieved, and fuel cell is improved performance.
Patent Information
- Application Number
- CN202210827701.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-07-13
AI Technical Summary
Bipolar plates in fuel cells are prone to flooding problems, resulting in the mass transfer of reaction gases being blocked and the battery performance is reduced.
The hydrophobic material was prepared using NiCo2O4/Ni composite material, and the hydrophobic material with a nanoneedle structure was formed by mixing and reacting with foam nickel, and used for the hydrophobic coating of the bipolar plate.
The hydrophobic material can stabilize the binding gas, form a thin "air cushion", reduce the free energy of the material surface, show excellent hydrophobicity and ice resistance, avoid residual liquid water droplets in the bipolar plate, and improve fuel cell performance.
Smart Images

Figure CN115188994B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a hydrophobic material and a preparation method and application thereof. Background Art
[0002] Proton exchange membrane fuel cells are mainly composed of membrane electrodes (including gas diffusion layers, catalyst layers and proton exchange membranes), bipolar plates and sealing materials. The bipolar plates mainly play the role of separating and transmitting reaction gases, collecting and conducting current, dissipating heat and drainage, and supporting membrane electrodes. Its flow field structure is mainly composed of ridges and flow channels. The ridges contact the gas diffusion layer, and the flow channels transmit the reaction gases. The gases pass through the gas diffusion layer to the three-phase junction for reaction. Therefore, the effective mass transfer of the reaction gases is of great help to improve the performance of fuel cells.
[0003] When the fuel cell is running, the reaction gas usually has a certain amount of humidification because the proton exchange membrane itself needs to be well moistened, so a large amount of water will be brought into the fuel cell. At the same time, the fuel cell itself will also produce water when reacting, and through reverse diffusion and electroosmotic drag, the water will be transferred between the anode and cathode. When there is too much water or liquid water droplets, the bipolar plate cannot discharge the excess water from the battery, which will block the pores of the porous medium, hinder the mass transfer of the reaction gas, cause flooding, and reduce battery performance. Summary of the invention
[0004] The purpose of the present application is to provide a hydrophobic material and a preparation method and application thereof, so as to solve the problem that fuel cells are prone to flooding.
[0005] An embodiment of the present invention provides a method for preparing the hydrophobic material as described above, the method comprising:
[0006] Put Ni (NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O、NH 4 F and urea are dissolved in a solvent to obtain a solution to be used;
[0007] The standby solution and nickel foam are mixed and reacted to obtain an intermediate sample;
[0008] heat treating the intermediate sample to obtain a hydrophobic material;
[0009] Wherein, the mixing reaction temperature and the heat treatment temperature respectively meet the set temperature so that the hydrophobic material has a nano needle structure.
[0010] Optionally, the Ni(NO3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O and NH 4 The mass ratio of F is 1:(1-3):(2-6).
[0011] Optionally, the method further includes: pre-treating the nickel foam to remove nickel oxide and impurities on the surface.
[0012] Optionally, the temperature of the mixed reaction is 100-120° C., and the time of the mixed reaction is 4-6 hours.
[0013] Optionally, the mixing of the standby solution and nickel foam to obtain an intermediate sample comprises:
[0014] The standby solution and the nickel foam are mixed and reacted, and then washed and dried for the first time to obtain an intermediate sample;
[0015] The temperature of the first drying is 60-70° C., and the time of the first drying is 10-12 hours.
[0016] Optionally, the temperature of the heat treatment is 300-350°C, and the time of the heat treatment is 2-3h.
[0017] Optionally, the heat treatment of the intermediate sample to obtain a hydrophobic material specifically includes:
[0018] The intermediate sample is subjected to heat treatment, and after natural cooling, a second drying is performed to obtain a hydrophobic material;
[0019] The temperature of the second drying is 100-120° C., and the time of the second drying is 5-6 hours.
[0020] Based on the same inventive concept, the embodiment of the present invention further provides a hydrophobic material, wherein the hydrophobic material comprises NiCo 2 O 4 / Ni composite material, the NiCo 2 O 4 / Ni composite material has a nano-needle structure.
[0021] Based on the same inventive concept, an embodiment of the present invention further provides a hydrophobic layer, and the material of the hydrophobic layer is the hydrophobic material as described above.
[0022] Based on the same inventive concept, an embodiment of the present invention further provides a bipolar plate, which includes a flow field plate, and a hydrophobic layer is coated on the surface of the flow field plate, and the hydrophobic layer is the hydrophobic layer as described above.
[0023] Based on the same inventive concept, an embodiment of the present invention further provides a method for preparing the bipolar plate as described above, the method comprising:
[0024] Pretreating the substrate to obtain an intermediate;
[0025] Performing a hydrophobic coating treatment on the intermediate to obtain a bipolar plate;
[0026] The hydrophobic coating treatment adopts a magnetron sputtering process, the bias voltage of the magnetron sputtering process is -50-300V, the power of the magnetron sputtering process is 0.8-1.5kW, and the vacuum degree of the deposition chamber back of the magnetron sputtering process is 10 -3 -10 -8 Pa, and the nitrogen flow atmosphere pressure of the magnetron sputtering process is 0.1-3Pa.
[0027] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0028] The method for preparing a hydrophobic material provided in an embodiment of the present invention has a nano-needle structure, and its composite micron structure has a continuous three-dimensional porous skeleton. The nickel cobalt oxide nanomaterial on the surface of the hydrophobic material has a large specific surface area, a large number of mesopores and other structural characteristics, so that this material can bind gas relatively stably, and then form a thin "air cushion" on the surface of the material, which reduces the surface free energy of the material and exhibits excellent hydrophobicity. When the material is used for the bipolar plate of a fuel cell, it is ensured that no liquid water droplets remain in the bipolar plate during the operation of the fuel cell, thereby avoiding liquid water blocking gas mass transfer, avoiding flooding, and improving the performance of the fuel cell.
[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 It is a performance curve diagram of the bipolar plates provided by Examples 1-3 of the present invention and Comparative Example 1;
[0032] Figure 2It is a flow chart of the method provided by the embodiment of the present invention. DETAILED DESCRIPTION
[0033] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0034] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0036] The technical solution of the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:
[0037] According to a typical embodiment of the present invention, a hydrophobic material is provided, wherein the hydrophobic material comprises NiCo 2 O 4 / Ni composite material, the NiCo 2 O 4 / Ni composite material has a nano-needle structure.
[0038] NiCo with nano-needle structure 2 O 4 / Ni composite materials have super hydrophobicity. The microstructure of the composite structure has a continuous three-dimensional porous skeleton, and the nickel cobalt oxide nanomaterial on the surface has a large specific surface area and a large number of mesopores. These structural characteristics enable this material to bind gas relatively stably, thereby forming a thin "air cushion" on the surface of the material, reducing the surface free energy of the material and showing excellent hydrophobicity and ice resistance.
[0039] According to another typical embodiment of the present invention, a method for preparing the hydrophobic material as described above is provided, the method comprising:
[0040] S0 pre-treating the nickel foam to remove nickel oxide and impurities on the surface;
[0041] Specifically, in this embodiment, commercial nickel foam is sequentially placed in acetone, hydrochloric acid, deionized water, and alcohol and ultrasonically treated for 15 minutes each to remove nickel oxide and impurities on the surface.
[0042] S1. Ni(NO3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O、NH 4 F and urea are dissolved in a solvent to obtain a solution to be used;
[0043] In some embodiments, the Ni(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O and NH 4 The mass ratio of F is 1:(1-3):(2-6).
[0044] S2. The standby solution and nickel foam are mixed to obtain an intermediate sample;
[0045] In some embodiments, the temperature of the mixing reaction is 100-120° C., and the time of the mixing reaction is 4-6 hours.
[0046] Generally speaking, after the mixing reaction is completed, the product needs to be washed and first dried. The temperature of the first drying is 60-70° C. and the time of the first drying is 10-12 hours.
[0047] Specifically, in this embodiment, the nickel foam is vacuum dried in a drying oven for 2 to 3 hours, and then Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and NH4F are dissolved in deionized water in a ratio of 1:1 to 3:2 to 6, and urea is added and stirred evenly for 0.5 to 1 hour to form a clear solution, and the solution is transferred to a reactor, and the nickel foam is added, and the reactor is moved into a drying oven, and reacted at 100 to 120°C for about 5 hours, and after it is naturally cooled, the sample in the reactor is taken out. After the sample is washed with ethanol and deionized water, it is placed in a 60 to 70°C drying oven and dried for 10 to 12 hours.
[0048] S3. heat-treating the intermediate sample to obtain a hydrophobic material.
[0049] In some embodiments, the heat treatment temperature is 300-350° C., and the heat treatment time is 2-3 hours.
[0050] Generally speaking, after the heat treatment is completed, the product needs to be subjected to a second drying process. The temperature of the second drying process is 100-120° C. and the time of the second drying process is 5-6 hours.
[0051] Specifically, in this embodiment, the sample is placed in a muffle furnace for heat treatment at a temperature of 300-350°C for 2-3 hours. After the heat treatment is completed, the sample is cooled naturally, taken out and placed in a vacuum drying oven, and vacuum dried at 100-120°C for 5-6 hours to obtain a super-hydrophobic material having a nano-needle-shaped nickel cobalt oxide / nickel foam composite structure.
[0052] According to another typical embodiment of the present invention, a hydrophobic layer is provided, wherein the material of the hydrophobic layer is the hydrophobic material as described above.
[0053] According to another typical embodiment of the present invention, a bipolar plate is provided, wherein the bipolar plate comprises a flow field plate, and a surface of the flow field plate is coated with a hydrophobic layer, wherein the hydrophobic layer is the hydrophobic layer as described above.
[0054] According to another typical embodiment of the present invention, a method for preparing the bipolar plate as described above is provided, the method comprising:
[0055] S21. Pretreating the substrate to obtain an intermediate;
[0056] S22. The intermediate is subjected to a hydrophobic coating treatment to obtain a bipolar plate;
[0057] The hydrophobic coating treatment adopts a magnetron sputtering process, the bias voltage of the magnetron sputtering process is -50-300V, the power of the magnetron sputtering process is 0.8-1.5kW, and the vacuum degree of the deposition chamber back of the magnetron sputtering process is 10 -3 -10 -8 Pa, and the nitrogen flow atmosphere pressure of the magnetron sputtering process is 0.1-3Pa.
[0058] The hydrophobic material of the present application and its preparation method and application will be described in detail below in combination with embodiments, comparative examples and experimental data.
[0059] Example 1
[0060] A method for preparing a bipolar plate, the method comprising:
[0061] 1) For the preparation of superhydrophobic materials: Place commercial nickel foam in acetone, hydrochloric acid, deionized water, and alcohol in turn and ultrasonicate for 15 minutes each to remove nickel oxide and impurities on the surface. Dry the nickel foam in a vacuum oven for 2 hours, then take Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and NH4F in a ratio of 1:2:2, dissolve in deionized water, add urea and stir evenly for 0.5-1h to form a clear solution, transfer the solution to the reactor, and add nickel foam. Move the reactor into a drying oven, react at 100-120°C for about 5 hours, wait for it to cool naturally, and take out the sample in the reactor. After washing the sample with ethanol and deionized water, put it in a 60°C drying oven and dry it for 12 hours. Then put it into a muffle furnace for heat treatment at a temperature of 300-350°C for 2 hours. After the heat treatment is completed, the sample is allowed to cool naturally, and then taken out and placed in a vacuum drying oven, and vacuum dried at 100-120° C. for 5-6 hours to obtain a super-hydrophobic material having a nano-needle-shaped nickel cobalt oxide / nickel foam composite structure.
[0062] 2) Preparation of hydrophobic coating for bipolar plates: Clean the formed bipolar plates, use deionized water, acetone, ethanol, and deionized water to wash repeatedly for 3 times and then dry; Treat the bipolar plates with hydrophobic coating: Use the super-hydrophobic material of the above-mentioned composite structure to prepare the coating by magnetron sputtering process. Further, the magnetron sputtering process includes: bias voltage of -50V to 300V, power of 0.8 to 1.5kW; further, the magnetron sputtering process includes: the vacuum degree of the back of the deposition chamber is 10-3Pa to 10-8Pa, and the nitrogen flow atmosphere is 0.1 to 3Pa.
[0063] Example 2
[0064] A method for preparing a bipolar plate, the method comprising:
[0065] 1) For the preparation of superhydrophobic materials: Place commercial nickel foam in acetone, hydrochloric acid, deionized water, and alcohol in turn and ultrasonicate for 15 minutes each to remove nickel oxide and impurities on the surface. Dry the nickel foam in a vacuum oven for 2 hours, then take Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and NH4F in a ratio of 1:1:2, dissolve them in deionized water, add urea and stir evenly for 0.5-1h to form a clear solution, transfer the solution to the reactor, and add nickel foam. Move the reactor into a drying oven, react at 100-120°C for about 5 hours, wait for it to cool naturally, and take out the sample in the reactor. After washing the sample with ethanol and deionized water, put it in a 60°C drying oven and dry it for 12 hours. Then put it into a muffle furnace for heat treatment at a temperature of 300-350°C for 2 hours. After the heat treatment is completed, the sample is allowed to cool naturally, and then taken out and placed in a vacuum drying oven, and vacuum dried at 100-120° C. for 5-6 hours to obtain a super-hydrophobic material having a nano-needle-shaped nickel cobalt oxide / nickel foam composite structure.
[0066] 2) Preparation of hydrophobic coating for bipolar plates: Clean the formed bipolar plates, use deionized water, acetone, ethanol, and deionized water to wash repeatedly for 3 times and then dry; Treat the bipolar plates with hydrophobic coating: Use the super-hydrophobic material of the above-mentioned composite structure to prepare the coating by magnetron sputtering process. Further, the magnetron sputtering process includes: bias voltage of -50V to 300V, power of 0.8 to 1.5kW; further, the magnetron sputtering process includes: the vacuum degree of the back of the deposition chamber is 10-3Pa to 10-8Pa, and the nitrogen flow atmosphere is 0.1 to 3Pa.
[0067] Example 3
[0068] A method for preparing a bipolar plate, the method comprising:
[0069] 1) For the preparation of superhydrophobic materials: Place commercial nickel foam in acetone, hydrochloric acid, deionized water, and alcohol in turn and ultrasonicate for 15 minutes each to remove nickel oxide and impurities on the surface. Dry the nickel foam in a vacuum oven for 2 hours, then take Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and NH4F in a ratio of 1:2:6, dissolve them in deionized water, add urea and stir evenly for 0.5-1h to form a clear solution, transfer the solution to the reactor, and add nickel foam. Move the reactor into a drying oven, react at 100-120°C for about 5 hours, wait for it to cool naturally, and take out the sample in the reactor. After washing the sample with ethanol and deionized water, put it in a 60°C drying oven and dry it for 12 hours. Then put it into a muffle furnace for heat treatment at a temperature of 300-350°C for 2 hours. After the heat treatment is completed, the sample is allowed to cool naturally, and then taken out and placed in a vacuum drying oven, and vacuum dried at 100-120° C. for 5-6 hours to obtain a super-hydrophobic material having a nano-needle-shaped nickel cobalt oxide / nickel foam composite structure.
[0070] 2) Preparation of hydrophobic coating for bipolar plates: Clean the formed bipolar plates, use deionized water, acetone, ethanol, and deionized water to wash repeatedly for 3 times and then dry; Treat the bipolar plates with hydrophobic coating: Use the super-hydrophobic material of the above-mentioned composite structure to prepare the coating by magnetron sputtering process. Further, the magnetron sputtering process includes: bias voltage of -50V to 300V, power of 0.8 to 1.5kW; further, the magnetron sputtering process includes: the vacuum degree of the back of the deposition chamber is 10-3Pa to 10-8Pa, and the nitrogen flow atmosphere is 0.1 to 3Pa.
[0071] Comparative Example 1
[0072] A method for preparing a bipolar plate, the method comprising:
[0073] Preparation of hydrophobic coating for bipolar plates: Clean the formed bipolar plates, use deionized water, acetone, ethanol, and deionized water to wash repeatedly for 3 times, and then dry; Treat the bipolar plates with hydrophobic coating: Use the commonly used hydrophobic material TiN and use a magnetron sputtering process to prepare the coating. Further, the magnetron sputtering process includes: bias voltage of -50V to 300V, power of 0.8 to 1.5kW; further, the magnetron sputtering process includes: the vacuum degree of the back of the deposition chamber is 10-3Pa to 10-8Pa, and the nitrogen flow atmosphere is 0.1 to 3Pa.
[0074] Experimental example
[0075] The bipolar plates provided in Examples 1-3 and Comparative Example 1 were tested for contact angles, and the results are shown in the following table.
[0076]
[0077]
[0078] It can be seen from the above table that the contact angle of the hydrophobic coating of the bipolar plate using this new composite hydrophobic material is higher than that of the control example, proving that it has higher hydrophobicity.
[0079] Attached Figure 1 Detailed description:
[0080] like Figure 1 As shown, the performance curves of the bipolar plates provided for Examples 1-3 and Comparative Example 1 are different. It can be seen from the figure that the reaction rates and stability regulated by different ratios of the embodiments are different, so the morphologies of the nickel salts formed are also different, and the contact angles and performances are different; due to better drainage performance, the mass transfer will be better, and the performance will be higher at high current density. At the same time, due to the high hydrophobicity, water droplets are not easy to stay, and the anti-icing performance is better than that of the comparative example.
[0081] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0082] The hydrophobic material provided by the embodiment of the present invention includes NiCo 2 O 4 / Ni composite material, the NiCo 2 O 4 / Ni composite material has a nano-needle structure. The bipolar plate coating with the nano-needle composite material has a continuous three-dimensional porous skeleton due to the microstructure of the composite structure, and the cobalt oxide nickel nanomaterial on the surface has a large specific surface area, a large number of mesopores and other structural characteristics, which enables this material to bind gas relatively stably, and then form a thin "air cushion" on the surface of the material, reducing the surface free energy of the material, showing excellent hydrophobicity and ice resistance. It ensures that no liquid water droplets remain in the bipolar plate during the operation of the fuel cell, avoids liquid water blocking gas mass transfer, avoids flooding, and improves the performance of the fuel cell. At the same time, the high hydrophobicity ensures that no water droplets remain, and further improves the anti-ice ability of the fuel cell during cold start.
[0083] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0084] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0085] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A bipolar plate, characterized in that: The bipolar plate includes a flow field plate, the surface of the flow field plate is coated with a hydrophobic layer, the hydrophobic material of the hydrophobic layer includes a NiCo2O4 / Ni composite material, the NiCo2O4 / Ni composite material has a nano needle structure, and the preparation method of the NiCo2O4 / Ni composite material includes: Dissolve Ni(NO3)2·6H2O, Co(NO3)2·6H2O, NH4F and urea in a solvent to obtain a ready-to-use solution; The standby solution and nickel foam are mixed and reacted to obtain an intermediate sample; heat treating the intermediate sample to obtain a hydrophobic material; Wherein, the mass ratio of Ni(NO3)2·6H2O, Co(NO3)2·6H2O and NH4F is 1:(1-3):(2-6); The temperature of the mixed reaction is 100-120° C., the time of the mixed reaction is 5 hours, the temperature of the heat treatment is 300-350° C., and the time of the heat treatment is 2 hours.
2. The bipolar plate according to claim 1, characterized in that: The heat treatment of the intermediate sample to obtain the hydrophobic material specifically includes: The intermediate sample is subjected to heat treatment, and after natural cooling, a second drying is performed to obtain a hydrophobic material; The temperature of the second drying is 100-120° C., and the time of the second drying is 5-6 hours.
3. The bipolar plate according to claim 1, characterized in that: The method for preparing the NiCo2O4 / Ni composite material further includes: pre-treating the nickel foam to remove nickel oxide and impurities on the surface.
4. The bipolar plate according to claim 1, characterized in that: The mixing of the standby solution and the nickel foam to obtain an intermediate sample specifically includes: The standby solution and the nickel foam are mixed and reacted, and then washed and dried for the first time to obtain an intermediate sample; The temperature of the first drying is 60-70° C., and the time of the first drying is 10-12 hours.
5. A method for preparing a bipolar plate according to any one of claims 1 to 4, characterized in that: The method comprises: Pretreating the substrate to obtain an intermediate; Performing a hydrophobic coating treatment on the intermediate to obtain a bipolar plate; The hydrophobic coating treatment adopts a magnetron sputtering process, the bias voltage of the magnetron sputtering process is -50-300V, the power of the magnetron sputtering process is 0.8-1.5kW, and the vacuum degree of the deposition chamber back of the magnetron sputtering process is 10 -3 -10 - 8 Pa, and the nitrogen flow atmosphere pressure of the magnetron sputtering process is 0.1-3Pa.